After successful hepatitis C virus antiviral therapy: It looks that normal alanine aminotransferase level is not the normal. Issue 3 (28th July 2017) - El Kassas, Mohamed; Alboraie, Mohamed; Mostafa, Aya; Ezzat, Reem; El Tahan, Adel; Afify, Shimaa; Sweedy, Ahmed; Kabbash, Ibrahim; Esmat, Gamal
Abstract : Background: Normal serum alanine aminotransferase (ALT) levels differ with age, gender, and body mass index. Adjusting the upper limits of normal (ULN) for ALT needs further research in different populations. Aim of this work was to monitor the effect of successful chronic hepatitis C (CHC) treatment on the ALT levels in patients with normal pretreatment ALT. Methods: Data of 1160 CHC patients with persistent pretreatment normal liver enzymes were retrospectively analyzed. Treatment response to direct acting antiviral agents (DAAs) therapy was recorded. Changes in ALT levels before and after treatment were analyzed by patients' demographic, laboratory, and radiologic characteristics. Areas under the receiver operating characteristic curve (AUROC) of ALT after treatment were used to generate a new ALT ULN. Results: Males were 568 (49%) and females 592 (51%) with a mean age of 50.7 years. After treatment, mean (±SD) of ALT levels significantly decreased from (26.3±7.8) to (19.1±10.9). This reduction was more significant in interferon‐free than interferon‐based regimens. ROC curve analyses suggested a new ALT ULN cut off (26.4 IU/L) in the treated patients (sensitivity=78.6%, specificity=83.8%, AUROC=0.89. This cutoff dropped to 14.7 IU/L in cirrhotic patients (sensitivity=77.4%, specificity=44.7%, AUROC=0.612). The identified cutoffs were 16.3 IU/L (sensitivity=66.7%, specificity=47.5%, AUROC=0.499) and 15.5 IU/L (sensitivity=76.5%, specificity=51.3%, AUROC=0.576) in males and females, respectively. Conclusion: The current ALT ULN needs readjustment to identify new normal cutoffs in CHC patients. Posttreatment cutoffs differ according to gender, pretreatment liver affection, and treatment regimen.